Symptoms of Anxiety and Depression among Italian UNiversity academics: the 2020 UN-SAD study. (20th October 2021) - Del Pin, M; Scarpis, E; Ruscio, E; Tullio, A; Brunelli, L; Brusaferro, S
Abstract: Background: The potential impact of demanding working conditions and career opportunities on the mental health of academic professionals has recently arisen some concerns, possibly resulting in psychological distress. This study aims to assess the prevalence of depression and anxiety within Udine University, comparing academic and administrative staff. Methods: A cross-sectional survey involving regular (RP) and short-term academic professionals (STP), and administrative staff (AS) was carried out between June and December 2020 throughout the administration of an online anonymous survey. Prevalence of depressive and anxiety symptoms was assessed using PHQ-9 and GAD-7 tools. Demographic information about age, gender, marital status and seniority was collected. Relationship between mental health outcomes and professional role was analysed using nonparametric tests and ordinal logistic regression. Results: All 5 university departments participated for a total of 366 people, being 109 of them STP, 146 RP and 111 AS. 55, 7% of them were female, with a mean age of 47, 9 years. Compared to administrative and regular staff, short-term professionals have a higher prevalence (95%CI) of both depressive (39, 4% (30, 8 - 48, 8) vs 14, 4% (9, 6 - 21, 0) vs 27, 0% (19, 6 - 35, 9); p < 0, 001) and anxiety symptoms (STP: 33, 0% (24, 9 - 42, 3); RP: 15, 1% (10, 2 - 21, 8); AS: 22, 5% (15, 8 - 31, 1); p < 0.005). Multivariate models suggest an increased risk of depression OR 1.61 (0.98-2.64) and anxiety OR 2.08 (1.27-3.41) for female. Conclusions: The higher prevalence of depressive and anxiety symptoms among STP could represent the effect on younger academics' mental health of the career uncertainty and challenging arena. The difference between AS and STP in psychological distress could be explained by the different job security status. More support should be given by universities to young academics for their both effective and healthy contribution to the progress of research. Key messages: The high level of external pressure, referred as "publish or perish", can play an important role in determining academics' mental health. Investment to provide coping tools for young academics could be strategical for researchers' empowerment.